Establishment of sandwich ELISA for soluble alpha-Klotho measurement: Age-dependent change of soluble alpha-Klotho levels in healthy subjects - Yamazaki, Yuji; Imura, Akihiro; Urakawa, Itaru; Shimada, Takashi; Murakami, Junko; Aono, Yukiko; Hasegawa, Hisashi; Yamashita, Takeyoshi; Nakatani, Kimihiko; Saito, Yoshihiko; Okamoto, Nozomi; Kurumatani, Norio; et al. (Biochemical and biophysical research communications, 2010)
► We established a detection system to measure human serum soluble α-Klotho (sαKl). ► We found that Age influences serum sαKl levels in a normal population. ► This detection system should be an excellent tool for investigating sαKl functions. α-Klotho (αKl) regulates mineral metabolism such as calcium ion (Ca 2+) and inorganic phosphate (Pi) in circulation. Defects in mice result in clinical features resembling disorders found in human aging. Although the importance of transmembrane-type αKl has been demonstrated, less is known regarding the physiological importance of soluble-type αKl (sαKl) in circulation. The aims of this study were: (1) to establish a sandwich ELISA system enabling detection of circulating serum sαKl, and (2) to determine reference values for sαKl serum levels and relationship to indices of renal function, mineral metabolism, age and sex in healthy subjects. We successively developed an ELISA to measure serum sαKl in healthy volunteers ( n = 142, males 66) of ages (61.1 ± 18.5 year). The levels (mean ± SD) in these healthy control adults were as follows: total calcium (Ca; 9.46 ± 0.41 mg/dL), Pi (3.63 ± 0.51 mg/dL), blood urea nitrogen (BUN; 15.7 ± 4.3 mg/dL), creatinine (Cre; 0.69 ± 0.14 mg/dL), 1,25 dihydroxyvitamin D (1,25(OH) 2D; 54.8 ± 17.7 pg/mL), intact parathyroid hormone (iPTH; 49.2 ± 20.6 pg/mL), calcitonin (26.0 ± 12.3 pg/mL) and intact fibroblast growth factor (FGF23; 43.8 ± 17.6 pg/mL). Serum levels of sαKl ranged from 239 to 1266 pg/mL (mean ± SD; 562 ± 146 pg/mL) in normal adults. Although sαKl levels were not modified by gender or indices of mineral metabolism, sαKl levels were inversely related to Cre and age. However, sαKl levels in normal children ( n = 39, males 23, mean ± SD; 7.1 ± 4.8 years) were significantly higher (mean ± SD; 952 ± 282 pg/mL) than those in adults (mean ± SD; 562 ± 146, P < 0.001). A multivariate linear regression analysis including children and adults in this study demonstrated that sαKl correlated negatively with age and Ca, and positively with Pi. Finally, we measured a serum sαKl from a patient with severe tumoral calcinosis derived from a homozygous missense mutation of α-klotho gene. In this patient, sαKl level was notably lower than those of age-matched controls. We established a detection system to measure human serum sαKl for the first time. Age, Ca and Pi seem to influence serum sαKl levels in a normal population. This detection system should be an excellent tool for investigating sαKl functions in mineral metabolism.